Step-up switched-capacitor multilevel inverter employing multiple inputs with reduced switches - Wang, Yaoqiang; Wang, Zhe; Liu, Wenjun; Zhang, Yun; Wang, Kewen; Liang, Jun (JOURNAL OF POWER ELECTRONICS, 2021)
A large device count, weak boosting capability, and DC voltage imbalance are common issues in conventional multilevel inverters. In this paper, a novel multilevel inverter is presented that can generate the desired number of output levels with reduced devices by using new switched-capacitor circuits (SCCs). The two input sources and capacitors in the SCC can be switched in parallel and series modes. In the parallel mode, the capacitor voltage of the SCC is charged to the DC source voltage, which inherently solves the capacitor voltage imbalance issue without any auxiliary circuits. In the series mode, the capacitor can be used as an alternative source, which helps achieve a high voltage gain. The multiple input sources of the SCC make the proposed topology suitable for application in renewable energy generation systems where several DC sources are available. Instead of an H-bridge module, a structure with two half-bridges and two switches is used as a polarity generation circuit at the load terminal. The input sources of two SCCs can be selected as symmetric and asymmetric patterns, which can result in a great number of output voltage levels. The circuit topology, operational principle, modulation strategy, capacitor analysis, and performance comparisons of the inverter are described in this paper. In addition, experimental results verify the feasibility and validity of the inverter.